Debunking Ford's relation to the past: history as "Bunk" in Emersonian perspective. Issue 4 (10th September 2021) - Watt, Peter
Abstract : Purpose: This paper aims to reconsider the significance of Henry Ford's claim that "History is more or less bunk". It argues that this seemingly philistine remark can be understood as a specific historiographical position which informed Ford's wider worldview, management approach and philosophy of industry. Design/methodology/approach: The paper draws on primary philosophical works, secondary criticism and archival evidence. These sources detail the context in which the claim was made, the ideas underpinning its articulation and the conceptual basis on which Ford's wider perspectives and contributions to historical experience can be interpreted. Findings: This paper interprets Ford's claim as a gesture of allegiance to a deeper cultural sensibility that was informed by Ralph Waldo Emerson's transcendental view of history. Practical implications: In addition to offering a rereading of Ford's historiographical position, Emerson's thought is discussed in relation to Ford's subsequent "living history" project (Greenfield Village), which is considered the materialisation of his historical and industrial worldview. Originality/value: This interpretation reveals how a specific historiographical position held by one of the twentieth century's leading industrialists offers new insights into his wider worldview and philosophy of industry. It contributes to recent studies that challenge taken-for-granted narratives in management history and recent work that has highlighted the influence of transcendental principles on Ford's philosophy of industry.